PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROJECT PADA TEMA 3 MAKANAN SEHAT DI KELAS V SD - Nurul Amelia Lubis; Sukmawarti sukmawarti (STKIP Subang, 2024)
This research aims to develop a project-based student worksheet on healthy food material for class V elementary school that is valid, effective and practical in improving student learning outcomes. This research uses the research and development (R & D) method using the ADDIE model. The research subjects for developing project-based Student Worksheets are media design experts, material experts. The object of this research is project-based Student Worksheets on the theme 3 healthy food. To analyze the data collected from the questionnaire it can be grouped into 2 types of data, namely descriptive qualitative and descriptive quantitative. Qualitative data was obtained from a questionnaire containing criticism and suggestions from media and material validator experts. Quantitative data is obtained from the formula used to determine the suitability of the material and media. The data obtained is used as a reference for making revisions to the products being developed. Based on the calculation results above, the overall assessment results from material experts reached 76%. If the percentage obtained reaches 61% to 80% then the material is categorized as feasible. Based on the validation results from media experts, the development of project-based Student Worksheets on theme 3 healthy food is suitable for use and suitable to be developed in learning theme 3 healthy food with a percentage of 76%. This means that learning media is included in the